Analysis of Sun Yingsha's Tactics and Countermeasures against Ito Meicheng: -- Taking 2019-2021 as an example - Du, Zi (Transactions on Social Science, Education and Humanities Research, 2024)
The Tokyo Olympics have come to an end, and the Chinese table tennis team has achieved excellent results of 4 gold and 3 silver medals. The end of the Olympic cycle represents the arrival of the next competition cycle, and Sun Yingsha has left a profound impression in various world competitions. Japanese player Meicheng Ito, who is the same year as Sun Yingsha, is a strong competitor to the Chinese women's table tennis team. Meicheng Ito has a fast, fierce, and fierce backhand style, and has repeatedly defeated Chinese women's table tennis players in world competitions, proving her strength. According to statistics, it has been found that since 2018, Sun Yingsha has only narrowly lost once against Ito Meicheng, indicating that she must have had a reason to win against Ito Meicheng. By analyzing the technical and tactical aspects of the four matches between representative post-00s athletes Sun Yingsha and Ito Meicheng in China and Japan from 2019 to 2021, this study aims to identify Sun Yingsha's technical and tactical characteristics, as well as her strengths and weaknesses. This article mainly adopts the methods of literature review, video observation, and three-stage indicator evaluation to analyze the technical and tactical aspects of Sun Yingsha's four singles matches against Japanese female table tennis player Meicheng Ito in the 2019 World Cup women's team final, the 2020 World Cup women's singles quarter finals, the 2021 Tokyo Olympics women's singles semi-finals, and the women's team final. The following conclusions are drawn: 1. The starting and grabbing stage is Sun Yingsha's main scoring stage, and the use of technical and tactical methods is clear. In serving and grabbing the third and fifth boards, serving is Sun Yingsha's major advantage. 2. Sun Yingsha performed well in the overall handling of receiving and serving during the receiving and grabbing phase, with outstanding performance being that she showed stability and high quality in both forehand scoring and attacking, as well as backhand rebounding and side grabbing on the backhand half platform. 3. During the stalemate stage, Sun Yingsha did not have the upper hand, but the difference between the two was not significant. The backhand was the main line of confrontation between Sun Yingsha and Ito Meicheng, but the score was not ideal. With more and more board turns, Sun Yingsha appeared impatient and made a move to strengthen the rotational quality too much, avoiding the confrontation during the stalemate.